Graft and Patient Outcomes of Kidney Transplant Tourism: A Single-Center Experience - Altheaby, Abdulrahman; Owaidah, Kenana; Alotaibi, Aljowharah; Salem, Rahaf; Algain, Rihaf; Alotaibi, Areij; Alnasrullah, Ahmad; Shaheen, Mohammed F.; Tawhari, Mohammed; Abdulgadir, Mohamad (Avicenna Journal of Medicine, 2022)
Background The supply-demand mismatch between organ donor and patient waiting for transplant has led to the growth of transplant tourism. This type of transplant is considered unethical and illegal, as it is usually performed in poor environments and carries a higher risk of infectious, vascular, and immunological complications.Methods In this single-centered retrospective cohort study, we compared patients who underwent transplant tourism to patients who were transplanted locally and followed up in our hospital from January 2015 to December 2018.Result A total of 254 local transplants and 60 patients from the transplant tourism group were included. Transplant tourism recipients were younger otherwise both groups were similar in gender, body mass index, diabetes, and hypertension. Recipients in the transplant tourism group had a significantly higher rate of delayed graft function (18.3% vs. 6.3%, p 0.005), acute rejection (40% vs. 7.9%, p < 0.001), and higher posttransplant infection in general. With more urological complications and higher graft failure at 3-years' follow-up (11.7% vs. 0.8%, p < 0.001).Conclusion Transplant tourism is associated with a higher risk of infection and poor graft outcomes. Extra efforts are required to cut down transplant tourism by educating patients about its clinical risk and ethical considerations. In addition, measures to increase the number of deceased donor pool to provide a better alternative options for patients are essential.
Keywords: kidney transplantation; transplant tourism; commercial transplant; posttransplant complications; graft survival